Cancer Vaccines: From the State of the Art to the Most Promising Frontiers in the Treatment of Colorectal Cancer - Eleonora Martinis; Carolina Ricci; Caterina Trevisan; Gaia Tomadini; Silvia Tonon (MDPI AG, 2023)
Colorectal cancer represents 10% of all new cancer cases each year and accounts for almost 10% of all cancer deaths. According to the WHO, by 2040 there will be a 60% increase in colorectal cancer cases. These data highlight the need to explore new therapeutic strategies. Classical interventions include surgical resection, chemotherapy and radiotherapy, which are invasive strategies that have many side effects on the patients and greatly affect their quality of life. A great advance in the treatment of this cancer type, as well as of all the others, could be the development of a vaccination strategy preventing the onset, the progression or the relapse of the pathology. In this review, we summarize the main vaccination strategies that are being studied for the treatment of colorectal cancer (CRC) and finally explore the possibility of using B-cells for the development of a new type of vaccine.